Blood-Brain Barrier Disruption, Sodium Fluorescein, And Fluorescence-Guided Surgery Of Gliomas. (4th March 2018) - Xiang, Yan; Zhu, Xiao-Peng; Zhao, Jian-Nong; Huang, Guo-Hao; Tang, Jun-Hai; Chen, Huan-Ran; Du, Lei; Zhang, Dong; Tang, Xue-Feng; Yang, Hui; Lv, Sheng-Qing
Abstract: Purpose: Sodium fluorescein (SF) is an ideal dye for intraoperative guided-resection of high-grade gliomas (HGGs). However, it is not well understood whether the SF-guided technique is suitable for different grades of gliomas, and the correlation between fluorescence and pathology is also not yet clear. Materials and methods: In this study, we investigated 28 patients, including 23 patients with HGG and 5 patients with low-grade glioma (LGG). All patients were treated using the SF-guided technique on a Pentero 900 microscope (Carl Zeiss, Oberkochen, Germany). Claudin-5 immunohistochemical (IHC) staining for the tumours and peritumour tissues was analyzed. Results: Intraoperative yellow fluorescence was noted in all the HGGs but not in the LGGs. Claudin-5 expression in the blood brain barrier endothelial cells was downregulated and disconnected in the HGGs ( p < 0.05), but had no difference or slightly decreased in the LGGs ( p > 0.05). Conclusions: The SF-guided technique is suitable for HGG surgery but not for LGG surgery. Downregulation of claudin-5 expression may contribute to the presence of yellow fluorescence in the glioma in SF-guided surgery.